Épistémologie et pédagogie chez Gaston Bachelard et Karl Popper - Alain Firode (Recherches en Éducation)
Although they have many things in common, Bachelard’s epistemology and Popper’s epistemology show distinct conceptions of science and scientific culture, which lead to different and sometimes opposite didactic implications. While Bachelard’s philosophy is consistent with the main trends of the currently prevailing doctrine in education (due to the educational role Bachelard gives to scientific culture), Popper’s philosophy, because of its objectivistic and logical implications, leads to a conception of science education that deeply departs from it.